Nomenclatural and taxonomic notes on Jacobaea borysthenica (Asteraceae) and some related taxa - Mosyakin, S.L.; Shiyan, N.M. (Український ботанічний журнал, 2019)
Following our recent lectotypification (with a specimen from G-DC) of the name Senecio praealtus Bertol. var.
borysthenicus DC. validated by de Candolle based on Andrzejowski's and Besser's specimens from Ukraine, we provide here
information on additional original specimens of that taxon (KW: Besser and Turczaninow historical collections), which is
now recognized as Jacobaea borysthenica (DC.) B.Nord. & Greuter and which was until recently widely accepted as Senecio
borysthenicus (DC.) Andrz. ex Czern. (Asteraceae). In particular, there are two isolectotypes in KW collected by Andrzejowski
near Kyslyakivka (now Lymany, Mykolayiv Region, Ukraine), as well as some other specimens collected near Zaporizhzhya
(Andrzejowski) and in southern Podolia (Besser and/or Andrzejowski). Some related Eastern European taxa of the taxonomically
complicated Jacobaea vulgaris Gaertn. (= Senecio jacobaea L.) aggregate and misapplied names are discussed as well. The
identity of the name Senecio divaricatus Andrz. (nom. illeg., non L.) is clarified; it is a synonym of Jacobaea borysthenica. It is
also confirmed that Senecio podolianus Panigrahi is an illegitimate replacement name for S. borysthenicus. Jacobaea borysthenica
seems to be closely related to J. andrzejowskyi (Tzvelev) B.Nord. & Greuter and J. vulgaris subsp. pannonica Hodálová & Mered'a;
the two latter taxa morphologically differ from J. borysthenica but are very similar to each other and may be even conspecific.
Further studies are needed for clarifying the complex evolutionary and biogeographical patterns within the J. vulgaris aggregate
in Eastern Europe and adjacent areas. На доповнення до нещодавно проведеної нами лектотипіфікації назви Senecio praealtus Bertol. var. borysthenicus DC. (зразок з гербaрію G-DC), що була запропонована О.П. де Кандоллем на основі зразків А.Л. Анджейовського та В.Г. Бессера з України, ми подаємо тут інформацію про додаткові оригінальні зразки цього таксона (KW: історичні гербарні колекції Бессера та Турчанінова), який зараз розглядається як Jacobaea borysthenica (DC.) B.Nord. & Greuter, а донедавна широко визнавався як Senecio borysthenicus (DC.) Andrz. ex Czern. (Asteraceae). Зокрема, у гербарії KW виявлено два ізолектотипи, зібрані Анджейовським біля Кисляківки (зараз Лимани, Миколаївська область, Україна), а також деякі інші зразки, зібрані біля Запоріжжя (Анджейовський) та на півдні Поділля (Бессер та/або Анджейовський). Обговорені деякі споріднені східноєвропейські таксони зі складу систематично складної групи Jacobaea vulgaris Gaertn. (= Senecio jacobaea L.) aggr., а також назви, що були невірно застосовані до нашого таксона. Прояснено таксономічний статус Senecio divaricatus Andrz. (nom. illeg., non L.): ця назва є синонімом Jacobaea borysthenica. Підтверджено, що Senecio podolianus Panigrahi є незаконною назвою, помилково запропонованою на заміну S. borysthenicus. Ймовірно, що вид Jacobaea borysthenica близько споріднений з J. andrzejowskyi (Tzvelev) B.Nord. & Greuter та J. vulgaris subsp. pannonica Hodálová & Mered'a; два останні морфологічно відмінні від J. borysthenica, але дуже подібні між собою, а може й належать до одного й того ж виду. Потрібні подальші дослідження для виявлення складної еволюційної та біогеографічної картини у межах видового комплексу J. vulgaris aggr. у Східній Європі та на прилеглих територіях.